Ambulatory blood pressure monitoring over 24 h: A Latin American Society of Hypertension position paper—accessibility, clinical use and cost effectiveness of ABPM in Latin America in year 2020. Issue 4 (12th February 2020) - Sánchez, Ramiro A.; Boggia, José; Peñaherrera, Ernesto; Barroso, Weimar Sebba; Barbosa, Eduardo; Villar, Raúl; Cobos, Leonardo; Hernández Hernández, Rafael; Lopez, Jesús; Octavio, José Andrés; Parra Carrillo, José Z.; Ramírez, Agustín J.; et al.
Abstract: Accurate office blood pressure measurement remains crucial in the diagnosis and management of hypertension worldwide, including Latin America (LA). Office blood pressure (OBP) measurement is still the leading technique in LA for screening and diagnosis of hypertension, monitoring of treatment, and long‐term follow‐up. Despite this, due to the increasing awareness of the limitations affecting OBP and to the accumulating evidence on the importance of ambulatory BP monitoring (ABPM), as a complement of OBP in the clinical approach to the hypertensive patient, a progressively greater attention has been paid worldwide to the information on daytime and nighttime BP patterns offered by 24‐h ABPM in the diagnostic, prognostic, and therapeutic management of hypertension. In LA countries, most of the Scientific Societies of Hypertension and/or Cardiology have issued guidelines for hypertension care, and most of them include a special section on ABPM. Also, full guidelines on ABPM are available. However, despite the available evidence on the advantages of ABPM for the diagnosis and management of hypertension in LA, availability of ABPM is often restricted to cities with large population, and access to this technology by lower‐income patients is sometimes limited by its excessive cost. The authors hope that this document might stimulate health authorities in each LA Country, as well as in other countries in the world, to regulate ABPM access and to widen the range of patients able to access the benefits of this technique.